Alkali‐Ion Batteries: SnO2 as Advanced Anode of Alkali‐Ion Batteries: Inhibiting Sn Coarsening by Crafting Robust Physical Barriers, Void Boundaries, and Heterophase Interfaces for Superior Electrochemical Reaction Reversibility (Adv. Energy Mater. 6/2020). Issue 6 (11th February 2020) - Zhao, Shiqiang; Sewell, Christopher D.; Liu, Ruiping; Jia, Songru; Wang, Zewei; He, Yanjie; Yuan, Kunjie; Jin, Huile; Wang, Shun; Liu, Xueqin; Lin, Zhiqun
Abstract : In article number 1902657, Shun Wang, Xueqin Liu, Zhiqun Lin, and co‐workers present three key strategies for inhibiting Sn coarsening to enhance the conversion and alloying reaction reversibility of SnO2 as an anode for alkali‐ion batteries by establishing robust physical barriers, constructing stable void boundaries, and introducing abundant heterophase interfaces.